REINFORCING STUDENTS’ SHORT FUNCTIONAL TEXT WRITING SKILL THROUGH MIND MAPPING TECHNIQUE - Syahara Dina Amalia, Regina F. Santos, Erlinda Yunita Dewi, Lintang Gita Ramadan (Universitas Muhammadiyah Surakarta, 2022)
This research is generally aimed at problem-solving and improvement attempts for students’ writing skill, especially in short functional text writing. In particular, it is also expected to contribute to the betterment of the teaching and learning processes of the Short Functional Text Writing subject in the Department of English Education (DEE) in the Faculty of Teacher Training and Education of Universitas Muhammadiyah Surakarta and as an alternative technique in teaching the subject for the lecturers. Class Action Research (CAR) is applied to identify whether using mind mapping can help reinforce students’ skill in writing short functional texts. The subject of this research is the first semester students who are being taught Short Functional Text Writing subject. The researchers gathered the data from two cycles in a qualitative manner. The data were obtained from the observation, the results of the tests and the questionnaire. The results of this research are that the students’ motivation increased since they could harness their creativity in making a variety of mind maps from different media and the students’ comprehension about short functional texts improved since mind mapping could help them understand the materials